MOBILE LEARNING TO IMPROVE WRITING IN ESL TEACHING - Noriega, Heidy Selene Robles (TEFLIN Journal, 2016)
This article reports on the results of a study concerning the type of texts and their features produced by a student after using mobile technology as a support to improve the development of the students’ writing skills in a second language. The Functional Systemic Linguistic (FSL), Genre Pedagogical Approach (GPA), and mobile learning concepts were employed as theoretical framework. The participant of the research was a freshman student that belongs to an English narrative course in a private university of the Caribbean region, Universidad Del Norte in Barranquilla, Colombia. This case study analyzed the student’s writing during a period of eight-week course, which was then complemented with an interview conducted by the researcher. The results reveal that genre approach can be implemented with mobile technology to increase students’ writing ability.